Analisis Prediksi Kebangkrutan Menggunakan Metode Altman (Z-Score) Pada Sub Sektor Batu Bara yang Terdaftar di BEI Periode 2013-2017 - Eka Purnama Sari (Universitas Batanghari Jambi, 2020)
This study aims to know and to analyze prediction of bankruptcy. This study took objects in of coal sub-sector listed on the Indonesia Stock Exchange for the period 2013 to 2017. As we know, the goal of company is not being bankrupt so that the company needed a method to predict the bankruptcy as soon as possible. One of the method is Z-Score Altman. In this study, the data used is secondary data. The data sources in this study are data from idx.co.id in the form of financial reports and annual reports in the Coal Sub Sector during the period 2013 to 2017. The analytical tool in this study is analysis by method Altman Z-Score. Five companies taken as sample is PT. Atlas Resources Tbk, PT. Delta Dunia Makmur Tbk, PT. Darma Henwa Tbk, PT. Bumi Resources Tbk, and PT. Baramulti Suksessarana Tbk. Based on the results and conclusions of the analysis using Altman Z-Score method showed that: PT Atlas Resaources Tbk in 2013 to 2017 have the potential to be bankrupt. PT. Darma Henwa Tbk in 2013 to 2017 have the potential to be bankrupt. PT. Bumi Resaources Tbk in 2013 to 2017 have the potential to be bankrupt. PT. Delta Dunia Makmur Tbk in 2013 to 2015 have the potential to be bankrupt, but in 2016 and 2017 PT. Delta Dunia Makmur Tbk were in vulnerable bankruptcy (grey area). PT. Baramulti Suksessarana Tbk in 2013 to 2017 are in healthy condition (non bankrupt).